Evaluation of serum cystatin-C and netrin-1 as predictive biomarkers for renal injury in children with beta-thalassemia major - Ameer J Shwayel; Abdulkareem M Jewad; Mohammed Q Abdulsattar (Journal of Applied Hematology, 2023)
BACKGROUND: Despite optimal transfusion and chelation therapy, beta-thalassemia patients still commonly experience various complications, including renal complications, which may affect their survival. This case–control study involved pediatric patients with beta-thalassemia major (β-TM). MATERIALS AND METHODS: This case–control study involved pediatric patients with β-TM, a total of 60 patient samples were randomly collected from the Genetic Hematology Center at the Dhi-Qar Health Directorate, with an age range of 1–14 years. In addition, 60 samples were collected from healthy children in the same age range as the control group. In this study, the glomerular injury was predicted by measuring the concentration of serum cystatin-C (Cys-C), and the tubular injury was predicted by measuring the concentration of serum netrin-1 (NTN-1). Routine markers, such as hemoglobin (Hb) level, ferritin, serum albumin, and creatinine, were also examined for the patients and the control group. RESULTS: The results showed a statistically significant increase in serum Cys-C in the patient group compared to the control group (P < 0.001) and a significant increase of serum NTN-1 in β-TM patients compared to the control group (P < 0.001). In addition, the study showed a statistically significant decrease in Hb, serum albumin, and creatinine and a significant increase in serum ferritin in the patients group compared to the control group. In conclusion, from the results of this study, we can conclude that the serum Cys-C and NTN-1 measurements can be used as predictive biomarkers for glomerular and tubular injury and increase with age. CONCLUSION: Predicting glomerular and tubular injury using the measurement of serum Cys-C and NTN-1 has improved significantly and advanced with age.